Teatro amador paulista (1963-1975): organização federativa, fazer teatral e resistência à ditadura - Vilela, Mauriney Eduardo (2018)
The history of the State of São Paulo’s amateur theater federative movement is described and analyzed in the period between 1963 and 1975. We will describe the action of the State Board of Theatre (CET), and go together with the creation and development of amateur theater federations and the Confederation of Amateur Theatre in the State of São Paulo (COTAESP), in addition to the meetings, congresses, and festivals of Amateur Theatre. In the analysis way, we seek to understand what made people (and groups) with such different proposals become organized, building associations, organizing conferences, doing festivals, and searching political and physical spaces, for a period of a dozen years. The analysis also seeks to define who did amateur theatre during this period, their motivations and goals, their themes, and languages. According to what was analyzed, the amateur performances seem to be immersing in the feelings of your public and contributed to advancements and changes in social relationships, even facing powerful opposition of a military dictatorship